Analisis Framing Robert N. Entman terhadap Kasus Kronologi Penganiayaan Anak di Bawah Umur pada Media Online kompas.com - Pamungkas, Ikbal (Jurnal Ilmiah Multimedia dan Komunikasi, 2023)
Case of violence against children is an incident that must be highlighted by the media, because this case involves very sensitive and important aspects in society. The media has a significant role in providing information, forming public opinion, and encouraging social change. This research aims to analyze the way kompas.com frames the chronological case of the abuse committed by Mario Dandy against David, who is a minor. Â This incident happened Â on Monday 20 February 2023 at the Green Permata Housing Complex, Pesanggarahan, South Jakarta at around 20:30 WIB. This research uses a qualitative method with a narrative approach, and implements constructivist paradigm. This research uses a content analysis method for news published by kompas.com regarding the abuse case committed by Mario Dandy against David. The analysis model used in this research is Robert N. Entman's analysis through news framing built by kompas.com with four stages of framing analysis model elements. Based on content analysis, this research finds that kompas.com uses framing that emphasizes empathy for victims, raises issues related to preventing violence against children, and places emphasis on legal aspects, as well as the responsibilities of the individuals involved. This media chooses words and images carefully to protect the privacy and identity of the victim.This research seeks to open insight into how online news media such as kompas.com plays a role in shaping public opinion and giving reactions to sensitive cases. By understanding how framing works, it is hoped that the results of this research can provide a deeper understanding of the influence of the media on public perception, as well as provide input for the development of more balanced, ethical and meaningful reporting.